2015
DOI: 10.1093/eurheartj/ehv206
|View full text |Cite
|
Sign up to set email alerts
|

Fractional flow reserve-guided management in stable coronary disease and acute myocardial infarction: recent developments

Abstract: Coronary artery disease (CAD) is a leading global cause of morbidity and mortality, and improvements in the diagnosis and treatment of CAD can reduce the health and economic burden of this condition. Fractional flow reserve (FFR) is an evidence-based diagnostic test of the physiological significance of a coronary artery stenosis. Fractional flow reserve is a pressure-derived index of the maximal achievable myocardial blood flow in the presence of an epicardial coronary stenosis as a ratio to maximum achievable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 86 publications
(126 reference statements)
0
39
0
1
Order By: Relevance
“…Atherosclerotic diseases such as CHD remain the leading cause of death worldwide; the lifetime risk of CHD is 67% in humans over 55 years of age. [27][28][29] Studies have shown that lncRNAs are vital regulatory factors in the progression of AS. [30][31][32] Thus, defining their functions might help to identify novel diagnostic and therapeutic targets for AS.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic diseases such as CHD remain the leading cause of death worldwide; the lifetime risk of CHD is 67% in humans over 55 years of age. [27][28][29] Studies have shown that lncRNAs are vital regulatory factors in the progression of AS. [30][31][32] Thus, defining their functions might help to identify novel diagnostic and therapeutic targets for AS.…”
Section: Discussionmentioning
confidence: 99%
“…As a common Tatins lipid-lowering drug, atorvastatin reduces cholesterol content in blood plasma by inhibiting synthesis of HMG-CoA reductase and cholesterol inside the liver, thereby facilitating LDL ingestion and catabolism and lowering LDL level by increasing quantity of LDL receptors on hepatocyte surface [8,9]. As a kind of piperazine derivative, trimetazidine can accelerate transformation of myocardial fatty acid metabolism in blood into glucose metabolism, inhibit generation of oxygen radicals, increase myocardial output quantity, stabilize intracellular environment, and improve myocardial functions [10].…”
Section: Discussionmentioning
confidence: 99%
“…Should we consider this presentation to be an acute coronary syndrome (ACS) related to the mid-LAD unstable plaque being the culprit lesion and implement percutaneous intervention (PCI), which in turn carries some risk, particularly in complex cases [1,2]? Or a TTC with a typical apical ballooning [3,4]-which pathogenic mechanism is believed to be linked to microvascular dysfunction [5] and catecholamine cardiotoxicity [6]-with a significant but innocent concomitant mid-LAD coronary artery disease and therefore treat medically?…”
Section: Presentation Of the Casementioning
confidence: 99%